An Evaluation of Chemicals for the Toxicity to Brown Snail (Helix aspersa Muller) on Grapevines - Schwartz, A.; Capatos, D. (South African Journal of Enology and Viticulture, 2017)
A field trial was carried out to evaluate chemicals for toxicity to Helix aspersa Miiller on vines. The comparison of treatments was complicated by major inequalities of snail counts. A weighted logistic regression method was, therefore, employed to identify significant differences among treatments. The highest percentage kill was obtained with metaldehyde applied as a paste onto each vine cordon. Copper sulphate spray at 5% and 10% strength gave comparable kill rates but was phytotoxic to the vegetative parts of the vine and consequently should be further evaluated as treatments restricted to the trunk of the vine only. Alphamethrin, azinphos-methyl and metaldehyde were unsatisfactory as sprays.